Preparation of children for elective surgery and hospitalisation: A parental perspective. (December 2022) - Kennedy, Martina; Howlin, Frances
Parents play a central role in the preparation of their child for hospitalisation and surgery. This research examined the parental perspective on educating their child for an elective admission to hospital for surgery. The study employed a qualitative descriptive design and sampled eight parents from a private hospital in Dublin, Ireland, prior to their child's discharge, after ear, nose and throat surgery. A thematic analysis revealed four themes: how parents educate themselves about surgery and hospital, factors influencing parent's decisions on the quantity of information to share, sources of education about hospitalisation and aspects of hospitalisation not discussed by parents. Findings indicated that although the internet was used as a general source of information, parents relied more on information provided by the hospital. Parents used their child's age, individual needs and level of autonomy to determine what information to communicate. Specific areas that parents found difficult to communicate included pain and fasting. This research highlights the need for hospitals to invest and support the delivery of parental education for children prior to surgery. Clarification of the children's nurses' role in the development, implementation and evaluation of education programmes that support education delivery in the home by parents is also warranted.